Pengaruh Pemberian Reward dan Motivasi terhadap Kinerja Karyawan Oada PT Prima Indo Papua di Kawasan Industri Makassar KIMA 4 - Novita Fransisca; Petrus Oktavianus H; Marchelyn Pongsapan (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
Human resources are one of the important aspects that must be managed optimally by organizations in order to provide maximum contribution to achieving company goals. In the current era of globalization, the level of competition between companies is increasingly fierce, requiring organizations to continuously improve the performance of their employees. This study focuses on two main research questions: how does reward provision affect employee performance at PT Prima Indo Papua and how does motivation provision affect employee performance at the company. The purpose of this study is to determine the extent to which rewards and motivation contribute to improving employee performance. The research variables consist of Reward (X1), Motivation (X2), and Employee Performance (Y). The research population was all 40 employees of PT Prima Indo Papua, while the research sample of 31 people was determined using a saturated sampling technique. The types of data used were primary data obtained through questionnaires and secondary data from company documents. Data analysis was carried out using a quantitative method through hypothesis testing, where the null hypothesis (Ho) was rejected if the significance value was <0.05. The results showed that reward provision had a positive and significant effect on employee performance with a significance value of 0.025 <0.05, so the alternative hypothesis (Ha1) was accepted. Similarly, the motivation variable has a positive and significant effect on employee performance with a significance value of 0.044 < 0.05, thus the alternative hypothesis (Ha2) is accepted. Thus, both rewards and motivation are proven to be important factors in improving employee performance at PT Prima Indo Papua. This study implies that company management needs to continue to pay attention to the reward and motivation systems implemented to ensure employee performance is maintained and continuously improved.